Environmentally relevant atrazine exposure leads to increases in DNA damage and changes in morphology in the hepatopancreas of crayfish (Faxonius virilis) - Mohammad N. Hadeed; Carlie L. Castiglione; Sayf Saleem; Diana H. Chammout; Mariana D. Muskovac; Karen G. Crile; Sara A. Abdulelah; Ali Maalhagh-Fard; Ebrahim Y. Rampuri; Gregory M. Grabowski; Rachelle M. Belanger (Environmental Advances, 2022)
The herbicide atrazine is widely used for controlling broad leaf weeds and increasing crop yields in agricultural areas. Atrazine enters aquatic environments through runoff, ground water discharge and seepage where concentrations have been recorded above 300 ppb. Exposure to the herbicide atrazine at environmentally relevant concentrations has been shown to negatively impact aquatic organisms, including crayfish. Because xenobiotics are concentrated in the crayfish hepatopancreas (digestive gland), we examined changes in morphology and DNA damage in hepatopancreatic tissue structure and cells following a 10-day exposure to atrazine (0, 10, 40, 80, 100 and 300 ppb). We found that there were marked morphological changes, post-exposure, for all atrazine concentrations tested. Hepatopancreatic tissue exhibited degenerated tubule epithelium with necrosis of microvilli, tubule lumen dilation, changes in tubular epithelium height and vacuolization of the epithelium. Likewise, we also performed a terminal deoxynucleotidyl transferase (TdT) mediated dUTP nick-end labeling (TUNEL) assay which showed the percentage of cells with DNA damage increased following atrazine exposure. Crayfish hepatopancreatic tissue displayed significant increases in TUNEL-positive cells following exposure to atrazine at 100 ppb and above. Overall, exposure to atrazine at environmentally relevant concentrations damages hepatopancreatic tissue. This impairment could lead to changes in biotransformation, detoxification, digestion and molting, subsequently reducing crayfish populations and negatively impacting the aquatic ecosystem.